Feasibility of remote support for electrophysiological ablation procedures during CoVid-19 pandemics. (14th October 2021) - Muessigbrodt, A; Demoniere, F; Finoly, S; Mommarche, M; Inamo, J
Abstract:  : The COVID-19 pandemics is a global challenge with a huge impact on medicine, politics, economy, education, travel and many other aspects of human life. The treatment of heart rhythm disorders has also been affected by the disease itself and by restrictions in order to constrain the spread of the virus. Catheter ablations of cardiac arrhythmias are nowadays frequently guided by electro-anatomic mapping systems. Technical staff with medical training, or medical staff with technical training, is needed to assist the operator. Travel restrictions due to current COVID-19 pandemics have limited the in person availability for technical support staff. To overcome these limitations we explored the feasibility of remote support with an internet based communication platform. A total of 9 patients (87, 5% male, mean age 66, 6 years) with different arrhythmias (atrial fibrillation, left atrial flutter, typical right atrial flutter, left ventricular tachycardia), having undergone ablation procedures between October 2020 and February 2021, were included. Acute procedural success was obtained in 9 out of 9 procedures. No complications occurred. Our experience with remote support for electro-anatomic mapping for complex electrophysiological ablation procedures, show the feasibility and safety of this approach. It increases the availability of technical support at reduced costs and a reduced CO2 footprint. Remote support for electro-anatomic mapping may therefore facilitate continuous care for patients with arrhythmias during the COVID-19 pandemics. Due to its advantages beyond COVID-19 pandemics related problems, it will likely play a greater role in the future. FUNDunding Acknowledgement: Type of funding sources: None.